2021
DOI: 10.5217/ir.2020.00030
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prediction of 1-year efficacy of tofacitinib for treating refractory ulcerative colitis

Abstract: UC who had started TOF treatments between May and November 2018. The observation periods lasted up to 52 weeks after TOF administration. Patients were refractory to multiple treatments, such as corticosteroids, biologic agents, and a calcineurin inhibitor. TOF was initiated at 20 mg a day and decreasing to 10 mg a day after 8 weeks or more. All immunesuppressive agents, such as corticosteroids, immunomodulators, biologic agents, and calcineurin inhibitors, were withdrawn before starting TOF treatment. Disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 10 publications
1
33
1
Order By: Relevance
“…Eleven studies 5, 6, 11-13, 15, 19, 20, 22-24 reported clinical remission rates (n = 755) (Supplementary Table 1). Remission was achieved in 34.7% of patients at week 8 (95% CI, 24.4-45.1; 9 studies 6, 11-13, 15, 19, 20 ,22 ,24 ) and in 47% at weeks 12 to 16 (95% CI, 40.3-53.6; 8 studies 5,6,11,13,15,19,22,23 ; Fig. 1).…”
Section: Primary Endpoint: Clinical Remissionmentioning
confidence: 96%
See 2 more Smart Citations
“…Eleven studies 5, 6, 11-13, 15, 19, 20, 22-24 reported clinical remission rates (n = 755) (Supplementary Table 1). Remission was achieved in 34.7% of patients at week 8 (95% CI, 24.4-45.1; 9 studies 6, 11-13, 15, 19, 20 ,22 ,24 ) and in 47% at weeks 12 to 16 (95% CI, 40.3-53.6; 8 studies 5,6,11,13,15,19,22,23 ; Fig. 1).…”
Section: Primary Endpoint: Clinical Remissionmentioning
confidence: 96%
“…2). At months 6 and 12, 50.8% of patients (95% CI, 42.1-59.5; 6 studies 5-7, 11, 12, 23 ) and 41.8% of patients (95% CI, 31.8-51.8; 3 studies 7,11,12 ), respectively, had sustained response.…”
Section: Clinical Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence of symptoms after an initial response that require therapeutic change 36,22 Worsening of symptoms with endoscopic, radiological or serological (CRP or FCAL) evidence of inflammation that led to escalation/change in medication 20 Failure Interruption of tofacitinib before the end of follow-up 36 Tofacitinib discontinuation due to symptom recurrence in patients in remission, non-response to tofacitinib treatment and serious adverse events 38 . CC-BY-NC 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Relapsementioning
confidence: 99%
“…Descriptors of tofacitinib efficacy outcomes across real-world studies. 675 676 Clinical response Decrease of ≥2 points38,39 , 3 PMS/ decrease >30% from baseline40,20,24 Decrease ≥1 point on RBS 38 /absolute RBS=0/1 from baseline36,20 Reduction in SSCAI of 323…”
mentioning
confidence: 99%